Georisks during road tunneling in weathered quartz sand rock with faults under high-head of groundwater - B. Yuan; Y.S. Xu; S.L. Shen; T. Hino (International Association of Lowland Technology, 2016)
This paper presents an investigation of georisks during mining tunnel construction in weathered quartz sand rock with faults at Fuyang, which is located at the southwest of Hangzhou, Zhejiang Province, China. Fuyang is a hilly region, where volcanic and intrusive rock masses are irregularly distributed, with the extensive development of fault zones and joint fractures. The Park Road Tunnels in Fuyang City will pass through the mountain in the city center and will be excavated in the lightly to weakly weathered quartz sand rock. The rocks are mainly crushable and are affected by fault zones and joint fractures. The fault zones and joints have large cavities filled with loose fragments and rich of fissure water. The rocks are classified into three grades based on the design code for road tunnels in China. The strength of the rock gradually decreases under the softening effect of abundant fissure water during construction. It was found that water ingress occurred at the entrance and the exit of the tunnel, the faults, and the contact zone between the hard and soft rock. Landslides had also occurred at the entrance and the exit of the tunnel in this case study.